2006
DOI: 10.1353/psc.2006.0024
|View full text |Cite
|
Sign up to set email alerts
|

Killer Whales in Hawaiian Waters: Information on Population Identity and Feeding Habits

Abstract: Killer whales (Orcinus orca) have only infrequently been reported from Hawaiian waters, and most of what is known about killer whales worldwide comes from studies in coastal temperate waters. Here we present 21 records of killer whales from within the Hawaiian Exclusive Economic Zone between 1994 and 2004. Killer whales were recorded nine months of the year, most around the main Hawaiian Islands. Although there were more records than expected during the period when humpback whales are abundant around the Islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 22 publications
7
52
0
Order By: Relevance
“…This was only the second sighting of this species in Hawaiian waters in surveys which first began in 2000 (Baird et al 2013a). We were able to photo-identify all individuals present, but there were no matches to our photo-identification catalog of this species in Hawai'i (Baird et al 2006). Combined with the relative infrequency of sighting of this species, this suggests these individuals are part of an open-ocean population.…”
Section: Overall Survey Effortmentioning
confidence: 79%
“…This was only the second sighting of this species in Hawaiian waters in surveys which first began in 2000 (Baird et al 2013a). We were able to photo-identify all individuals present, but there were no matches to our photo-identification catalog of this species in Hawai'i (Baird et al 2006). Combined with the relative infrequency of sighting of this species, this suggests these individuals are part of an open-ocean population.…”
Section: Overall Survey Effortmentioning
confidence: 79%
“…Different ecotypes or species of orca have been recognised or proposed, based on not only morphological but also behavioural, foraging, and acoustical aspects (e.g., Baird, 2000;Ford, 2008). Offshore/Pelagic ecotypes have been proposed (e.g., Baird, 2001;Baird et al, 2006;Visser et al, 2010), with three different ecotypes identified in Antarctic waters (Berghan & Visser, 2001;Pitman & Ensor, 2003). A circumpolar Austral ecotype is being investigated in southern waters (Fair, 2010;Pitman et al, 2010;Visser, 2010a;Young & Egan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hector's beaked whale (Mesoplodon hectori) Gales et al 2002 Killer whale (O. orca) Barrett-Lennard et al 1996;Worthy and Abend 1997;Hoelzel et al 1998Hoelzel et al , 2002Chivers et al 2000;Ross et al 2000;Pitman 2003;Baird et al 2006;Pitman et al 2007 Worthy andAbend 1997 (note: blubber was analyzed because skin was unavailable), Herman et al 2005;Krahn et al 2007aKrahn et al , b, 2008Krahn et al , 2009 Barrett-Lennard et al…”
mentioning
confidence: 99%